2011
DOI: 10.1007/s00705-011-1030-z
|View full text |Cite
|
Sign up to set email alerts
|

First report of the complete sequence of Sida golden yellow vein virus from Jamaica

Abstract: Begomoviruses are phytopathogens that threaten food security [18]. Sida spp. are ubiquitous weed species found in Jamaica. Sida samples were collected island-wide, DNA was extracted via a modified Dellaporta method, and the viral genome was amplified using degenerate and sequence-specific primers [2, 11]. The amplicons were cloned and sequenced. Sequence analysis revealed that a DNA-A molecule isolated from a plant in Liguanea, St. Andrew, was 90.9% similar to Sida golden yellow vein virus-[United States of Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Begomoviruses have been reported in association with betasatellites in Malvastrum, including Malvastrum leaf curl virus with Malvastrum leaf curl betasatellite, Malvastrum yellow mosaic virus with Malvastrum yellow mosaic betasatellite (Guo et al 2007), Malvastrum yellow vein virus with Malvastrum yellow vein betasatellite (Wu et al 2007;Zhou et al 2003;Jiang and Zhou 2004), Malvastrum yellow vein Yunnan virus with Malvastrum yellow vein Yunan betasatellite (Jiang and Zhou 2005;Wu et al 2007), Tomato yellow leaf curl China virus with Tomato yellow leaf curl China betasatellite (Liu et al 2009;Yang et al 2011;Cui et al 2004;Dong et al 2007) and Malvastrum leaf curl Guangdong virus with Malvastrum leaf curl Guangdong betasatellite (Wu et al 2007). Recent findings indicate that the bipartite, New World begomoviruses Malvastrum yellow mosaic Jamaica virus (Fiallo-Olivé et al 2012;Graham et al 2010), Sida golden mosaic Florida virus (Fiallo-Olivé et al 2010) and Sida golden yellow vein virus (Fiallo-Olivé et al 2012;Stewart et al 2011) can also infect Malvastrum coromandelianum. Finally, the monopartite begomoviruses Malvastrum yellow mosaic Helshire virus (Graham et al 2010), Ageratum yellow vein virus (Yang et al 2008;Andou et al 2010;Saunders et al 2000) and Malvastrum leaf curl Philippines virus (Brown et al 2015) have been found as a single genomic component (without an associated DNA satellite) in Malvastrum.…”
mentioning
confidence: 99%
“…Begomoviruses have been reported in association with betasatellites in Malvastrum, including Malvastrum leaf curl virus with Malvastrum leaf curl betasatellite, Malvastrum yellow mosaic virus with Malvastrum yellow mosaic betasatellite (Guo et al 2007), Malvastrum yellow vein virus with Malvastrum yellow vein betasatellite (Wu et al 2007;Zhou et al 2003;Jiang and Zhou 2004), Malvastrum yellow vein Yunnan virus with Malvastrum yellow vein Yunan betasatellite (Jiang and Zhou 2005;Wu et al 2007), Tomato yellow leaf curl China virus with Tomato yellow leaf curl China betasatellite (Liu et al 2009;Yang et al 2011;Cui et al 2004;Dong et al 2007) and Malvastrum leaf curl Guangdong virus with Malvastrum leaf curl Guangdong betasatellite (Wu et al 2007). Recent findings indicate that the bipartite, New World begomoviruses Malvastrum yellow mosaic Jamaica virus (Fiallo-Olivé et al 2012;Graham et al 2010), Sida golden mosaic Florida virus (Fiallo-Olivé et al 2010) and Sida golden yellow vein virus (Fiallo-Olivé et al 2012;Stewart et al 2011) can also infect Malvastrum coromandelianum. Finally, the monopartite begomoviruses Malvastrum yellow mosaic Helshire virus (Graham et al 2010), Ageratum yellow vein virus (Yang et al 2008;Andou et al 2010;Saunders et al 2000) and Malvastrum leaf curl Philippines virus (Brown et al 2015) have been found as a single genomic component (without an associated DNA satellite) in Malvastrum.…”
mentioning
confidence: 99%